Knowledge, Perception, and Behavior of Business Consumers towards Meltique Meat in the City and District of Bogor - A. Apriantini; R. Maulidawafi; W. Humayrah; N. C. Dainy; E. L. Aditia (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2024)
Meltique meat is a type of meat that undergoes a special process that involves injecting fat into the muscle fibers of the meat. Business consumers use Meltique meat as an alternative to Wagyu meat because it is affordable but has similar characteristics to Wagyu meat. This study aims to analyze the relationship of meat knowledge and perception to business consumer behavior in the Bogor area. This study used 60 samples of food business consumers hotels, restaurants, catering, supermarkets, traditional markets, and meat suppliers in the Bogor area. The questionnaire results were analyzed using the Spearman rank correlation test to determine the relationship between knowledge and perceptions of business consumer behavior. The results showed that there was a strong unidirectional relationship between knowledge and perception of meltique meat on business consumer behavior in the Bogor area with rs=0.509 and rs=0.531. The significance value of P <0.05 indicates that consumer knowledge and perceptions have areal influence on business consumer purchasing behavior of meltique meat.